Brain asymmetry in the white matter making and globularity - Theofanopoulou, Constantina (Frontiers in Psychology, 2015)
Recent studies from the field of language genetics and evolutionary anthropology have put forward the hypothesis that the emergence of our species-specific brain is to be understood not in terms of size, but in light of developmental changes that gave rise to a more globular braincase configuration after the split from Neanderthals-Denisovans. On the grounds that (i) white matter myelination is delayed relative to other brain structures and in humans is protracted compared with other primates and (ii) neural connectivity is linked genetically to our brain/skull morphology and language-ready brain, I take it that one significant evolutionary change in Homo sapiens’ lineage is the interhemispheric connectivity mediated by the Corpus Callosum. The size, myelination and fiber caliber of the Corpus Callosum presents an anterior-to-posterior increase, in a way that inter-hemispheric connectivity is more prominent in the sensory motor areas, whereas “high- order” areas are more intra-hemispherically connected. Building on evidence from language-processing studies that account for this asymmetry (‘lateralization’) in terms of brain rhythms, I present an evo-devo hypothesis according to which the myelination of the Corpus Callosum, Brain Asymmetry and Globularity are conjectured to make up the angles of a co-evolutionary triangle that gave rise to our language-ready brain.